The Psychological Contract of Generation Z: Does HR Communication Meet the Legal and Moral Expectations of Young Employees? - Priyanto; Liling Listyawati; Damajanti Sri Lestari; Galuh ajeng Ayuningtyas; Dedi Setyawan (Faculty of Law, Universitas Pekalongan, 2023)
The entry of Generation Z into the workforce has reshaped organizational expectations surrounding Human Resource (HR) communication, emphasizing not only legal compliance but also ethical alignment. This study investigates how HR communication practices—both legal and moral—impact psychological contract fulfillment (PCF) and key employee outcomes among Generation Z in Indonesia. Employing a quantitative, correlational-explanatory design, data were collected via a structured online survey from 250 Gen Z employees across sectors and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both legal and moral fulfillment in HR communication significantly enhance PCF, which in turn positively influences job satisfaction and organizational commitment, while reducing intention to leave. Furthermore, PCF mediates the relationship between HR communication and these outcomes, confirming its pivotal role in shaping employee attitudes and behaviors. These results align with Psychological Contract Theory and Expectancy Theory, demonstrating that for Generation Z, employment relationships are grounded as much in values and transparency as in formal policy. The study contributes to the limited Southeast Asian literature on psychological contracts and offers actionable insights for HR practitioners to build value-oriented communication strategies that foster engagement, trust, and retention among younger employees.